Re-evaluation of a 2014 multi-country European outbreak of Salmonella Enteritidis phage type 14b using recent epidemiological and molecular data - Hörmansdorfer, Stefan; Messelhäußer, Ute; Rampp, Albert; Schönberger, Katharina; Dallman, Tim; Allerberger, Franz; Kornschober, Christian; Sing, Andreas; Wallner, Peter; Zapf, Andreas (Euro surveillance, 2017)
A European multi-country outbreak of Salmonella Enteritidis phage type (PT) 14b occurred from March to November 2014 associated with the consumption of eggs. The outbreak involved more than 400 human cases from France, Luxembourg, Austria and the United Kingdom. In 2016-2017, it has been re-evaluated combining recent epidemiological results with latest molecular data. The outbreak was traced back to one large Bavarian egg producer with four distinct premises, three located in Bavaria, one in the Czech Republic. The outbreak isolates of S. Enteritidis PT 14b were grouped into three closely related clades by whole genome sequencing. Two of these clades could be referred to two Bavarian premises of the egg producer on the basis of epidemiological and molecular data, while epidemiological data presumably linked the third clade to another premises of the egg producer. Interestingly and in contrast to the situation in other European countries where several outbreaks were documented, all notified 91 laboratory-confirmed cases of S. Enteritidis PT 14b from Bavaria were sporadic, singular cases not belonging to any epidemiological outbreaks. In conclusion, as demonstrated here, the resolution of food-related outbreaks with such a high discriminatory power is rare in outbreak investigation.
Keywords: Animals; vejce; Luxembourg; Salmonella Food Poisoning; United Kingdom; salmonelóza; Salmonella Infections; Whole Genome Sequencing; jednonukleotidový polymorfismus; lidé; Austria; Polymorphism, Single Nucleotide; Francie; otrava salmonelou; Spojené království; Salmonella enteritidis; Lucembursko; Disease Outbreaks; Czech Republic; sekvenování celého genomu; Bacteriophage Typing; Eggs; France; Česká republika; epidemický výskyt choroby; zvířata; fagotypizace; Rakousko; Humans